2021
DOI: 10.1038/s41390-021-01547-x
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of stroke and mortality in pediatric critical care patients with COVID-19 in Peru

Abstract: Introduction Pediatric critical care patients with COVID-19 treated in Peru have higher mortality than those previously reported from other countries. Pediatric providers have reported a high number of patients without comorbidities presenting with hemorrhagic strokes associated with COVID-19. We present a study analyzing the factors associated with mortality in this setting. Methods Prospective case–control study that included patients <17 years old admitted to a pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our findings parallel the paediatric COVID-19 mortality differences between HICs and LMICs described by Kitano and suggest that lower PICU mortality in HICs might not translate to LMICs. 12 Besides some Brazilian cohorts with a socioeconomic profile similar to HIC populations, most studies from LMICs demonstrate higher mortality, with younger age identified as a mortality risk 8 , 9 , 10 , 22 , 23 , 24 , 25 . We achieved significant representation from Latin America, a region largely ignored in prior paediatric studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings parallel the paediatric COVID-19 mortality differences between HICs and LMICs described by Kitano and suggest that lower PICU mortality in HICs might not translate to LMICs. 12 Besides some Brazilian cohorts with a socioeconomic profile similar to HIC populations, most studies from LMICs demonstrate higher mortality, with younger age identified as a mortality risk 8 , 9 , 10 , 22 , 23 , 24 , 25 . We achieved significant representation from Latin America, a region largely ignored in prior paediatric studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed age-related mortality differences are consistent with data from LMICs, and these regional differences deserve further investigation to understand the causative factors. 12 , 23 Since mortality for those without MIS-C appear similar across age ranges, it seems more likely that age-related mortality differences are due to the higher frequency and better survival rates of MIS-C in children >2 years old rather than worse survival rates for other forms of critical COVID-19 in younger children although further research is needed to explore this association.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias of observational studies and the control arm of trials was assessed using a checklist developed by the United States National Heart, Lung, and Blood Institute ( 13 ), which classifies studies as high (Poor), moderate (Fair), and low (Good) risk of bias. Cross-sectional and case series require 14 items, while cohort studies require nine items and case-control studies require 12 items.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, there is no mention of the effects the lack of KAP has already caused in Peru. Examples of some studies include: Infodemic 1 , 2 , 3 Self-medication 4 , 5 Medicinal plants use 6 , 7 , 8 , 9 Use of unproven treatments such as chlorine dioxide 6 , 10 Issues in children with the development of MIS-C 11 , 12 , 13 , 14 Impact in mental health 15 , 16 , 17 , 18 , 19 Technostress 20 Issues in adequate implementation of public health measures 21 , 22 , 23 Furthermore, Peru is leading some interesting aspects compared to Latin America in the implementation of telemedicine 24 , 25 , 26 , 27 …”
mentioning
confidence: 99%